2023
DOI: 10.18240/ijo.2023.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of corneal dermoid with lenticules from small incision lenticule extraction surgery: a surgery assisted by fibrin glue

Abstract: AIM: To observe the clinical efficacy of the combined use of small incision lenticule extraction (SMILE)-derived lenticule patches in corneal dermoid excision, with fixation of the lenticule patches assisted by fibrin glue. METHODS: Seventeen eyes of 17 patients with corneal dermoid were treated with dermoid removal combined with SMILE-derived lenticule transplantation. All lenticule patches were fixed by fibrin glue. Ocular changes were assessed using slit lamp microscopy and anterior-segmental optical cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…But in recent years, the corneal lenticules which is a transplant layer from the intrastromal corneal tissue, might be a useful and simpler alternative corneal graft substitute. It was reported that SMILE-derived lenticule had been applied as corneal graft in several corneal dermoid surgeries, but its safety and feasibility is not clear till now 12 . Besides, due to the limited thickness of the corneal lenticules, overlapped multi-layer lenticules are required to repair the corneal defect.…”
Section: Introductionmentioning
confidence: 99%
“…But in recent years, the corneal lenticules which is a transplant layer from the intrastromal corneal tissue, might be a useful and simpler alternative corneal graft substitute. It was reported that SMILE-derived lenticule had been applied as corneal graft in several corneal dermoid surgeries, but its safety and feasibility is not clear till now 12 . Besides, due to the limited thickness of the corneal lenticules, overlapped multi-layer lenticules are required to repair the corneal defect.…”
Section: Introductionmentioning
confidence: 99%